INOVASI DIGITAL DALAM PENGELOLAAN PIUTANG PADA UMKM UNTUK MENINGKATKAN PRODUKTIVITAS DAN KEBERLANJUTAN KEUANGAN - Iryanie, Emy; Heldalina, Heldalina; Fitria, Fitria (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2024)
According to data from the Ministry of Cooperation and SMEs, there will be 65.4 million UMKM in Indonesia in 2019, which can absorb a total of 123.3 thousand workers from the enterprise unit. This shows that UMKM has a major impact on the reduction in the unemployment rate in Indonesia. On the other hand, current technological developments can also be a booster for activity in the field of UMKM. In their business activities, many UMKMs conduct transactions and financial recording manually, which, of course, has the potential for mismatches in the recording and is considered less effective. Therefore, with the qualitative method and data analysis with one of the models of system development, namely waterfall, the author conducted this research and obtained results in line with the previous research that the presence of an account receivable management information system can help the management carry out account receivable recording procedures well, fast, and efficiently, so that it is expected to increase productivity and sustainability of the enterprise and can easily do account receivable administration